Analysis of Threshold Characteristics of Short-Wavelength Semiconductor Lasers - Bangguo Wang; Shaoyang Tan; Li Zhou; Wuling Liu; Lihong Zhu; Guoliang Deng; Jun Wang (IEEE Photonics Journal, 2024)
Existing high-power semiconductor lasers widely use asymmetric large cavity structures or designs with short cavity lengths to enhance device performance, inevitably increasing the device threshold current density and suppressing further improvement of device performance. We have utilized rate equations analysis to investigate the impact of threshold current density on the threshold characteristic temperature of GaAs-based laser diodes at short wavelengths. A simplified carrier escape model has been employed, which is more accurate compared to the classical model of thermal carrier emission. Compared to long-wavelength laser diodes, short-wavelength laser diodes exhibit higher temperature stability due to their smaller Auger recombination coefficients. Increased internal losses caused by carrier escape and decreased injection efficiency are the main reasons for the decrease in threshold characteristic temperature with increasing temperature. The increase in threshold significantly enhances carrier escape, leading to a decrease in the threshold characteristic temperature and an increase in sensitivity to temperature. Moreover, high thresholds limit the increase in the device's decoupling factor, causing a decrease in current inject efficiency and further degradation of device performance. By increasing the barrier height, carrier escape can be effectively suppressed, thereby enhancing device performance. The simulation results agree well with the experimental data of InAlGaAs laser diodes at a wavelength of 780 nm, accurately predicting the threshold characteristics of devices with different cavity lengths at various temperatures.